1982
DOI: 10.1111/j.1471-4159.1982.tb06635.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Iron Deficiency on Serotonin Uptake In Vitro by Rat Brain Synaptic Vesicles

Abstract: The effects of moderate and severe degrees of iron deficiency on brain and liver nonhaem iron levels and 5-hydroxytryptamine (serotonin; 5-HT) uptake by synaptic vesicles in vitro were investigated in experimental rats. Data obtained suggested that in both moderate and severe forms of iron deficiency, 5-HT uptake by brain synaptic vesicles is decreased and is accompanied by a reduction in brain and liver nonhaem iron levels. On repletion with iron for 4 weeks, the deficient group of rats showed a normalisation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1985
1985
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 27 publications
2
10
0
Order By: Relevance
“…Analogous results for serotonin (SHT) were reported by Kaladhar & Rao (93). SHT is also an important neurotransmitter whose function is linked to slow-wave sleep.…”
Section: Binding Of Biogenic Amines To Receptor Sitessupporting
confidence: 53%
See 2 more Smart Citations
“…Analogous results for serotonin (SHT) were reported by Kaladhar & Rao (93). SHT is also an important neurotransmitter whose function is linked to slow-wave sleep.…”
Section: Binding Of Biogenic Amines To Receptor Sitessupporting
confidence: 53%
“…This deficit is unusual in that it cannot be reversed, even after other manifestations of iron deficiency have been corrected by iron treatment. The physiological implications of this finding remain uncertain since the relatively few other biochemical manifestations of iron deficiency in brain that have been described are reversed with iron administration (83,92,93).…”
Section: Synthesis and Catabolism Of Biogenic Aminesmentioning
confidence: 87%
See 1 more Smart Citation
“…Serotonin transporters affected by iron deficiency in males included those in the olfactory tubercle, lateral parabrachial nucleus, superficial gray of the superior colliculus, optic tract, nucleus accumbens and cerebral cortex (Kaladhar 1982(Kaladhar ,1983. For the first three of these areas, iron repletion failed to restore the values to normal.…”
Section: Discussionmentioning
confidence: 97%
“…Low brain iron in the seizure-prone strain of rats is potentially very significant because brain has a variety of iron-containing proteins involved in oxidative metabolism; an impairment in oxidative metabolism could have a serious impact on neuronal function. As reported in a recent review of trace elements in brain metabolism (Prohaska, 1987), efforts to study neurotransmitter metabolism in iron deficiency have been few and inconclusive, although roles for iron in dopamine receptor binding (Youdim et al, 1983) and in serotonin storage (Kaladhar and Rao, 1982) have been suggested.…”
Section: Discussionmentioning
confidence: 99%